Development of Two Types of Skin Cancer in a Patient with Systemic Sclerosis: a Case Report and Overview of the Literature - Firdevs Ulutaş; Erdem Çomut; Veli Çobankara (Case Reports in Oncological Medicine)
Systemic sclerosis (SSc) is an uncommon rheumatic disease in which the underlying main histopathologic feature is a thickening of the skin due to excessive accumulation of collagen in the extracellular tissue. Fibrogenesis, chronic inflammation, and ulceration may eventually promote skin neoplasms. Although nonmelanoma skin cancer (NMSC) is the most frequent type, there have been restricted case reports and case series with skin cancers in SSc patients in the literature. Herein, we describe a 78-year-old woman diagnosed with diffuse cutaneous systemic sclerosis thirteen years ago and associated nonspecific interstitial pneumonia that was successfully treated with high cumulative doses of cyclophosphamide. She developed basal cell carcinoma and squamous cell carcinoma of the skin in the follow-up. She is still on rituximab treatment with stable interstitial lung disease as indicated by pulmonary function tests and high-resolution chest computed tomography. To our knowledge and a literature search, this is the first reported patient with SSc with two types of skin cancer. In this review, we also aimed to emphasize the relationship between SSc and skin cancer, and possible risk factors for SSc-related skin cancer.